2003
DOI: 10.1007/s00436-003-0839-0
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of Cryptosporidium parvum genotype I in conventionally reared piglets and lambs

Abstract: Parasites of the genus Cryptosporidium are intracellular parasites that occur throughout the animal kingdom and have been reported in many species of mammals, including human. Most infections in humans are caused by two C. parvum genotypes, genotype I and genotype II; these are the human and the bovine (zoonotic) genotypes, respectively.Successful experimental infection of Cryptosporidium parvum genotype I ''human genotype'' is described in four conventionally reared piglets and in a lamb. The inoculum was ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…This is the first report, to our knowledge, of a natural C. hominis infection in sheep, although recently, several groups have shown that lambs can be experimentally infected with C. hominis (2,11,17). Cryptosporidium hominis is the only Cryptosporidium species/genotype detected in the present study that is known to regularly infect humans (42) and as only one isolate was identified, this indicates that the public health risk from contamination of catchment areas, effluent and also abattoirs is probably low.…”
Section: Discussionmentioning
confidence: 74%
“…This is the first report, to our knowledge, of a natural C. hominis infection in sheep, although recently, several groups have shown that lambs can be experimentally infected with C. hominis (2,11,17). Cryptosporidium hominis is the only Cryptosporidium species/genotype detected in the present study that is known to regularly infect humans (42) and as only one isolate was identified, this indicates that the public health risk from contamination of catchment areas, effluent and also abattoirs is probably low.…”
Section: Discussionmentioning
confidence: 74%
“…Even though the lack of ability to infect mice and goats in cross-transmission studies was used as evidence for the separation of C. andersoni from C. muris (111), thus far it has been difficult to infect cattle of different ages and breeds with C. andersoni of bovine origin (9). The earlier conclusion that C. hominis does not infect experimental animals such as mice, calves, lambs, and pigs is apparently premature, since recent studies have clearly shown that calves, lambs, and piglets can be infected with C. hominis (3,55). "Genotype switching" (a different genotype of oocysts obtained after inoculation with one genotype of oocysts) has also been observed in cross-transmission studies (63,244).…”
Section: Species Concept In Cryptosporidiummentioning
confidence: 99%
“…Unlike C. parvum, C. hominis is traditionally considered noninfective for mice, rats, cats, dogs, and cattle (73,146,185,241,242). However, more recently, C. hominis has been reported from a dugong and a lamb, and calves, lambs, and piglets can also be infected experimentally with at least some C. hominis isolates at high doses (3,55,73,142). Pathogenicity studies with gnotobiotic pigs have shown the prepatent period to be longer than for C. parvum (8.8 and 5.4 days, respectively) and have also shown differences in parasite-associated lesion distribution and intensity of infection (146,186).…”
Section: Cryptosporidium Species Of Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subdivision of C. parvum into two species, C. hominis and C. parvum, has recently been proposed to replace the type 1 and 2 subspecies designations, respectively (23). C. hominis is considered as not naturally infective for animals with few exceptions and, experimentally, some C. hominis isolates were infective at high doses for calves, lambs, and piglets but not for cats, dogs, and rodents, with some exceptions (3,8,12,13,14,22,23,27,32,36). To our knowledge, the present findings represent the first report of reproducible and stable experimental C. hominis infection in the Mongolian rodent gerbil.…”
mentioning
confidence: 99%